SOURCE CREDIBILITY IN HEALTH PROMOTION INFORMATION DISSEMINATION: A SYSTEMATIC REVIEW (SLR) - Mohd Razif Zakaria, Normah Mustaffa, Emma Mirza Wati Mohamad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This systematic literature review study emphasized the Source Credibility (SC) in the dissemination of health information. The objective of this peer-to-peer review is to analyse the importance of SC in the dissemination of health information. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) is used as the method of study. Web of Science (WoS) and Scopus databases were the two main sources for retrieving the articles. The study found 19 articles and 28 articles in Scopus and WoS. After the screening process, only 5 articles met the criteria. All of the rejected articles were duplicated - in book form, book chapter, proceedings paper; did not comply with the stated themes (SC, trustworthiness, competence, attractiveness, and dynamism); articles based on non-empirical data focused on technical measurement; and failure to retrieve full article due to access problems. The study found SC is one of the factors that enables users to validate whether the health information credible or vice versa. However, various themes were identified as themes in the present study that will make the health information source credible, such as competence, trustworthiness, wordiness, as well as source attractiveness